Faktor-faktor Berhubungan dengan Praktik Penggunaan Kondom pada Kelompok Risiko Tinggi (Wanita Pekerja Karaoke dan Café) dalam Pencegahan Penyakit Menular Seksual (PMS) - Tutik Setyowati; Teguh Wahyudi; Sutarmi Sutarmi (Jurnal Riset Kesehatan, 2015)
The purpose of this study is to describe the practice of the use of condoms in high-risk groups (women workers karaoke and cafe) in the prevention of sexually transmitted diseases, HIV/AIDS in Blora in the café and karaoke in Blora. This research is descriptive correlation with cross-sectional approach. Selection of study subjects were made in total sampling as many as 35 people. Subjects of this study were women who worked in nightclubs as a waitress café, cafe guides and karaoke singer in Blora in 2014. Data was analysed using Chi Square Test. The results showed that there was a relationship between knowledge (p=0.001), attitudes (p=0.002), support of health workers (p=0.009) and support of clients (p=0.001) with the practice of condom use in high-risk groups (women workers karaoke and cafes) in the prevention of STDs, HIV/AIDS. It is suggested that the need for the provision of information on women who work in karaoke about the danger of STDs, HIV/AIDS. Moreover it is important to provide the availability of information about the use of condoms by the client when performing sexual transactions. It is suggested for the next researchers to study the qualitative research on this area.